Chronic Exposure to Deoxynivalenol Has No Influence on the Oral Bioavailability of Fumonisin B(1) in Broiler Chickens - Antonissen, Gunther (Toxins (Basel), 2015)
Both deoxynivalenol (DON) and fumonisin B(1) (FB(1)) are common contaminants of feed. Fumonisins (FBs) in general have a very limited oral bioavailability in healthy animals. Previous studies have demonstrated that chronic exposure to DON impairs the intestinal barrier function and integrity, by affecting the intestinal surface area and function of the tight junctions. This might influence the oral bioavailability of FB(1), and possibly lead to altered toxicity of this mycotoxin. A toxicokinetic study was performed with two groups of 6 broiler chickens, which were all administered an oral bolus of 2.5 mg FBs/kg BW after three-week exposure to either uncontaminated feed (group 1) or feed contaminated with 3.12 mg DON/kg feed (group 2). No significant differences in toxicokinetic parameters of FB(1) could be demonstrated between the groups. Also, no increased or decreased body exposure to FB(1) was observed, since the relative oral bioavailability of FB(1) after chronic DON exposure was 92.2%.